PENGGUNAAN MEDIA RODA PUTAR UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA POKOK BAHASAN HIDROKARBON DI KELAS XI IPA MAN 2 INDRAGIRI HILIR - Riyadhatul Jannah; Betty Holiwarni; Sri Haryati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Research on the use of rotary wheel media has been done with the aim to know to improve learner’s learning outcomes on the subject of hydrocarbons in class XI MAN 2 Indragiri Hilir. Form of the research was experimental research using Pretest-posttest Randomized Control Group Design. The sample consisted of two homogeneous classes, namely class XI IPA 1 as the experimental class and XI IPA 3 as the control class. The experimental class is a class that is applied to the use of the wheel while the control class is not use the wheel media. The data analysis technique used is t-test. The results of data processing obtained tcount > ttable that is 2,70 > 1,68, means that the use of rotary wheel media can improve learning results of learners on the subject of hydrocarbons class XI MAN 2 Indragiri Hilir with the category of increase in learning outcomes is a high category with a normalized gain (N-gain) of 0,82. Keywords: Rotary Wheel Media, Learning Results, Hydrocarbons.